Absent in Politics and Power : Political Exclusion of Indian Muslims - Rahman, Abdur, (Brill | Manohar Publishers & Distributors, 2024)
Muslims face acute political deprivation at all levels in spite of their immense contribution towards the survival of democracy in India. The volume attempts to gauge and analyze the political underrepresentation of Muslims in the Parliament and state assemblies as well as their nomination by the mainstream national and regional parties. The book analyzes the reasons responsible for their absence in politics and power, including their under-nomination in secular parties, denial of SC status to them, Muslim-majority seats being reserved for SCs, etc. The book also discusses the rise of the BJP and, its exclusionary attitude, communalization of political space and its fall out on the attitude of the secular parties, which thrive on Muslim votes. It also focuses on the internal factors within Muslims, such as presence of many Muslim candidates in Muslim-dominated seats, division of secular votes, lack of leadership, and their inability to forge a viable political alliance with other deprived groups. The volume also attempts to analyze the rise of upper caste Hindus in politics, political deprivation of Hindu OBCs, and necessity of due share of Pasmanda Muslims in politics for secularization of political space. The author delves closely into what strategies Muslims must adopt to have at least proportional share and introspection on how to create an effective political space. The volume advocates a forceful change of attitude, thinking and action on the part of various factors involved: government, political parties, media, academic circles, the community itself and other deprived sections. Finally, the book advocates for inclusive democracy and social democracy, as advocated by Dr. Ambedkar to eradicate inequality in politics and to have an all-representative government.